2019
DOI: 10.1016/j.ymgme.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic and anaplerotic dietary modifications ameliorate seizure activity in Drosophila models of mitochondrial encephalomyopathy and glycolytic enzymopathy

Abstract: Seizures are a feature not only of the many forms of epilepsy, but also of global metabolic diseases such as mitochondrial encephalomyopathy (ME) and glycolytic enzymopathy (GE). Modern antiepileptic drugs (AEDs) are successful in many cases, but some patients are refractory to existing AEDs, which has led to a surge in interest in clinically managed dietary therapy such as the ketogenic diet (KD). This high-fat, low-carbohydrate diet causes a cellular switch from glycolysis to fatty acid oxidation and ketone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 62 publications
0
8
0
1
Order By: Relevance
“…These ketone bodies can cross the blood–brain barrier and are used as a source of energy in the absence of glucose ( Gu et al, 2009 ). A recent study has reported that supplementation with triheptanoin simulates the effects of ketogenic-diet even in the presence of standard carbohydrates level ( Fogle et al, 2019 , Wehbe and Tucci, 2019 ). Replenishing of TCA-cycle intermediates augments the synthesis of ATP which essentially causes the stabilization of membrane potential and contributes to the anticonvulsant mechanism of the triheptanoin and substrates of the TCA-cycle as shown in Fig.…”
Section: Metabolic Therapiesmentioning
confidence: 99%
“…These ketone bodies can cross the blood–brain barrier and are used as a source of energy in the absence of glucose ( Gu et al, 2009 ). A recent study has reported that supplementation with triheptanoin simulates the effects of ketogenic-diet even in the presence of standard carbohydrates level ( Fogle et al, 2019 , Wehbe and Tucci, 2019 ). Replenishing of TCA-cycle intermediates augments the synthesis of ATP which essentially causes the stabilization of membrane potential and contributes to the anticonvulsant mechanism of the triheptanoin and substrates of the TCA-cycle as shown in Fig.…”
Section: Metabolic Therapiesmentioning
confidence: 99%
“…This might be explained by accumulation of genetic modifiers over time. Alterations in food composition are also known to affect seizure phenotype in flies and potential differences in fly food could also impact secondary phenotypes observed ( Stone et al, 2013 ; Fogle et al, 2019 ; Kasuya et al, 2019 ). On the other hand, the overall trend we observed matches previously reported data where seizure mutants are, overall, less active than controls ( Radlicz et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Very recent studies in drosophila models of mitochondrial encephalopathy and glycolytic enzymopathy have shown that supplementation of triheptanoin mimics the success of the ketogenic diet even in the presence of standard carbohydrate levels due to its anaplerotic effect . Moreover, triheptanoin does not appear to alter glucose metabolism in the healthy brain .…”
Section: Methodsmentioning
confidence: 99%
“…AR, anaplerotic reaction; ATP, adenosine triphosphate; BKP, β-ketopentanoate; BHP, β-hydroxypentanoate; CII, complex II of the electron transport chain; NADH/FADH 2 , nicotinamide adenine dinucleotide/flavin adenine dinucleotide; TCA, citric acid cycle effect. 10 Moreover, triheptanoin does not appear to alter glucose metabolism in the healthy brain. 11 Of note, the mechanism of action of triheptanoin depends on the modality of administration.…”
Section: Metabolism Of Triheptanoinmentioning
confidence: 98%